2010
DOI: 10.1021/jp1043046
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of NCN3 as a High-Temperature NCN Radical Source: Singlet−Triplet Relaxation and Absorption Cross Section of NCN(3Σ)

Abstract: The potential of the thermal decomposition of cyanogen azide (NCN3) as a high-temperature cyanonitrene (NCN) source has been investigated in shock tube experiments. Electronic ground-state NCN(3Σ) radicals have been detected by narrow-bandwidth laser absorption at overlapping transitions belonging to the Q1 branch of the vibronic 3Σ+−3Π subband of the vibrationally hot 3Πu(010)−3Σg−(010) system at = 30383.11 cm(-1) (329.1302 nm). High-temperature absorption cross sections σ have been directly measured at total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(70 citation statements)
references
References 49 publications
3
66
1
Order By: Relevance
“…Meanwhile, reaction (1b) has been experimentally proven to be the main product channel of reaction (1) [6][7][8][9][10]. Simultaneously, experimental work on NCN reactions has been carried out [11][12][13][14][15][16][17]. Besides the photolysis of diazomethane (CH 2 N 2 ) in the presence of cyanogen (C 2 N 2 ), the photolysis or pyrolysis of NCN 3 served as a source of NCN radicals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, reaction (1b) has been experimentally proven to be the main product channel of reaction (1) [6][7][8][9][10]. Simultaneously, experimental work on NCN reactions has been carried out [11][12][13][14][15][16][17]. Besides the photolysis of diazomethane (CH 2 N 2 ) in the presence of cyanogen (C 2 N 2 ), the photolysis or pyrolysis of NCN 3 served as a source of NCN radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Since the NCN precursor molecules yield NCN in its electronically excited single state, 1 NCN, the formation of the combustion-relevant 3 NCN requires subsequent relaxation to the triplet ground state. In thermal systems, noticeable equilibrium concentrations of the singlet species can be ruled out due to a large singlettriplet splitting of about 121 kJ/mol [15]. Both from a theoretical and a practical point of view the question arises how fast the singlet triplet relaxation occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the employed difference UV absorption setup, which was operated with about 1 mW output power of a frequency-doubled continuous-wave ring dye laser, have been described elsewhere [19]. The observed absorption band of the triplet NCN ground state is a superposition of the [23].…”
Section: Methodsmentioning
confidence: 99%
“…The observed absorption band of the triplet NCN ground state is a superposition of the [23]. The corresponding strongly temperature dependent but nearly pressure independent absorption cross section, log (σ (base e)/(cm 2 mol −1 )) = 8.9 − 8.3 × 10 −4 × T/K, has been adopted from previous work [19]. Note that this value was recently put into question by Lamoureux et al [24] who reported a 2.6 higher value based on elaborated theoretical spectroscopic calculations referenced to the electronic transition moment obtained from zero pressure fluorescence lifetime measurements by Smith et al [25].…”
Section: Methodsmentioning
confidence: 99%